Positive and negative regulatory regions control the spatial distribution of polygalacturonase transcription in tomato fruit pericarp. - Montgomery, J (1993)
The tomato fruit consists of a thick, fleshy pericarp composed predominantly of highly vacuolated parenchymatous cells, which surrounds the seeds. During ripening, the activation of gene expression results in dramatic biochemical and physiological changes in the pericarp. The polygalacturonase (PG) gene, unlike many fruit ripening-induced genes, is not activated by the increase in ethylene hormone concentration associated with the onset of ripening. To investigate ethylene concentration-independent gene transcription in ripe tomato fruit, we analyzed the expression of chimeric PG promoter-beta-glucuronidase (GUS) reporter gene fusions in transgenic tomato plants. We determined that a 1.4-kb PG promoter directs ripening-regulated transcription in outer pericarp but not in inner pericarp cells, with a sharp boundary of PG promoter activity located midway through the pericarp. Promoter deletion analysis indicated that a minimum of three promoter regions influence the spatial regulation of PG transcription. A positive regulatory region from -231 to -134 promotes gene transcription in the outer pericarp of ripe fruit. A second positive regulatory region from -806 to -443 extends gene activity to the inner pericarp. However, a negative regulatory region from -1411 to -1150 inhibits gene transcription in the inner pericarp. DNase I footprint analysis showed that nuclear proteins in unripe and ripe fruit interact with DNA sequences within each of these three regulatory regions. Thus, temporal and spatial control of PG transcription is mediated by the interaction of negative and positive regulatory promoter elements, resulting in gene activity in the outer pericarp but not the inner pericarp of ripe tomato fruit. The expression pattern of PG suggests that, although they are morphologically similar, there is a fundamental difference between the parenchymatous cells within the inner and outer pericarp.